Use of the energy of parametric oscillations to improve drilling indices - Svitlytskyi, V; Ohorodnikov, P; Kovalchuk, Yu (National Mining University, 2018)
Purpose. Increase of the efficiency of using energy of parametric oscillations within the assembly of drilling string bottom by means of solving nonlinear-parametric equations of a “bit – drive motor – drilled-out rock” system to improve drilling indices. Methods. The paper applies the method of mathematical modeling of a mechanical system as well as impedance method to study oscillations. While modeling the system, a bit is considered to be an absolutely solid body; elastic elements are non-inertial, drive motor is ideal, and resistance in elastic relations is viscous. While modeling dynamic parameters of a drill string and its interaction with a near-bit system and bottom hole, mechanical system is represented in the form of blocks interacting with each other. Drill string in models is a sequential system of uniform rods. Findings. In the course of analytical studies, it has been proved that use of energy of parametric oscillations within the assembly of drilling string bottom makes it possible to increase axial load on a bit as well as rise mechanical velocity especially while drilling horizontal areas of inclined boreholes. Dynamic parameters of mechanical system of a drill string and its interaction with near-bit system and bottom hole have been substantiated. It has been determined that limitation of the amplitude of resonant vertical oscillations for a bit is possible at the expense of toothed surface of cone rollers in terms of periodical positioning from one tooth to two teeth, physical and mechanical pro-perties of the drilled-out rocks, and features of correcting elements mounted above the bit. Originality. Innovative mathematical model describing dynamics of the operation of a “bit – drive motor – drilled-out rock” mechanical system has been developed taking into consideration the effect of parametric oscillations. Practical implications. Limited amplitude of resonant vertical oscillations of a bit is the condition of efficient assembly operation and long service life of its components in the context of parametric excitations. The obtained results may be useful while designing drill rigs.

Мета. Підвищення ефективності використання енергії параметричних коливань у компоновці низу бурильної колони шляхом розв’язання нелінійно-параметричних рівнянь системи “долото – приводний двигун – розбурювана порода” для підвищення показників буріння. Методика. В роботі використано метод математичного моделювання механічної системи та імпедансний метод дослідження коливань. При моделюванні системи долото вважається абсолютно твердим тілом, пружні елементи – безінерційними, приводний двигун – ідеальним, а опір у пружних зв’язках – в’язким. При дослідженні динамічних параметрів бурильної колони та її взаємодії з наддолотною системою і вибоєм механічна система представлена у вигляді блоків, які взаємодіють поміж собою. Бурильна колона в моделях становить послідовну систему однорідних стрижнів. Результати. В ході аналітичних досліджень було доведено, що використання енергії параметричних коливань у компоновці низу бурильної колони дає можливість збільшити осьове навантаження на долото та підвищити механічну швидкість, особливо під час буріння горизонтальної частини похило спрямованих свердловин. Обґрунтовано динамічні параметри механічної системи бурильної колони та її взаємодії з наддолотною системою і вибоєм. Виявлено, що обмеження амплітуди резонансних вертикальних коливань досягається долотом за рахунок зубчатої поверхні шарошок при періодичному переступанні з одного зуба на два, фізико-механічних властивостей розбурюваних порід і властивостей коректуючих елементів, встановлених над долотом. Наукова новизна. Розроблено нову математичну модель, що описує динаміку роботи механічної системи “долото – приводний двигун – розбурювана порода” з урахуванням впливу параметричних коливань. Практична значимість. Наявність обмеження амплітуди резонансних вертикальних коливань долота створює умови працездатності компоновок і довговічності її елементів із параметричними коливаннями. Отримані результати можуть бути корисними при проектуванні бурових конструкцій.

Цель. Повышение эффективности использования энергии параметрических колебаний в компоновке низа бурильной колонны путем решения нелинейно-параметрических уравнений системы “долото – приводной двигатель – разбуриваемая порода” для повышения показателей бурения. Методика. В работе использован метод математического моделирования механической системы и импедансный метод исследования колебаний. При моделировании системы долото считается абсолютно твердым телом, упругие элементы – безинерционными, приводной двигатель – идеальным, а сопротивление в упругих связях – вязким. При исследовании динамических параметров бурильной колонны и ее взаимодействия с наддолотной системой и забоем механическая система представлена в виде блоков, которые взаимодействуют между собой. Бурильная колонна в моделях составляет последовательную систему однородных стержней. Результаты. В ходе аналитических исследований было доказано, что использование энергии параметрических колебаний в компоновке низа бурильной колонны позволяет увеличить осевую нагрузку на долото и повысить механическую скорость, особенно при бурении горизонтальной части наклонно-направленных скважин. Обоснованы динамические параметры механической системы бурильной колонны и ее взаимодействия с наддолотной системой и забоем. Выявлено, что ограничения амплитуды резонансных вертикальных колебаний достигается долотом за счет зубчатой поверхности шарошек при периодическом перешагивании с одного зуба на два, физико-механических свойств разбуриваемых пород и свойств корректирующих элементов, установленных над долотом. Научная новизна. Разработано новую математическую модель, описывающую динамику работы механической системы “долото – приводной двигатель – разбуриваемая порода” с учетом влияния параметрических колебаний. Практическая значимость. Наличие ограничения амплитуды резонансных вертикальных колебаний долота создает условия работоспособности компоновок и долговечности ее элементов с параметрическими колебаниями. Полученные результаты могут быть полезными при проектировании буровых конструкций.
Keywords: drill string; bit; borehole; bottom hole motor; screw motor; load; turbobit